PENGARUH PROFITABILITAS, EFISIENSI BIAYA, DAN BAGI HASIL TERHADAP JUMLAH DEPOSITO MUDHARABAH PADA BANK UMUM SYARIAH PERIODE 2010-2014 - INDAH PUSPITA RISKYA, NUR (Jurnal Akuntansi AKUNESA, 2016)
This research aimed to know identify and expain the influnce of profitability, efficiency cost, and for the results to the amount od deposid mudharabah in the common sharia banks. Method used in this research is purposive sampling. The object of research is islamic banks using secondary data from the publication of financial statements starting from of 2010-2014. The data analysis was method intervening and analysis double linier regression. Result of this research showed that profitability variable, efficiency cost variable, for the result variable have no effect towards the amount of deposid mudharabah.